Mechanisms of Appendicular Dermal Bone Loss and Endochondral Bone Expansion during the Fin-To-Limb Transition - Lalonde, Robert (Université d'Ottawa / University of Ottawa, 2018)
The evolution of the tetrapod limb from paired fish fins involved drastic changes to the appendicular dermal and endochondral skeleton. Fish fin rays were lost, and the endochondral bone was modified and elaborated to form three distinct segments common to all tetrapod limbs: the stylopod, the zeugopod, and the autopod. Identifying the molecular mechanisms that contributed to these morphological changes presents a unique insight into our own evolutionary history. Chapter II of this thesis focuses on the actinodin gene family and how their disappearance from the tetrapod genome during the fin-to-limb transition may have contributed to the loss of dermal fin rays. The actinodin genes code for structural proteins in the actinotrichia, rigid fibers being the first exoskeletal elements formed during zebrafish fin development. We have identified tisse-specific cis-acting regulatory elements responsible for actinodin1 activation in the fin fold ectoderm and mesenchyme. These elements are only partially functional in transgenic reporter mouse limbs. We therefore propose that changes to actinodin gene regulation contributed to the loss of the actinodin genes during limb evolution. The actinotrichia also serve as a scaffold for the migration of cells from the distal fin mesenchyme, which has been shown to differentiate into fin ray osteoblasts. In fact, both actinotrichia and distal fin mesenchyme migration defects have been proposed as events that may lead to the loss of dermal bone during the fin-to-limb transition. Chapter III of this thesis tests the effects of distal fin mesenchyme ablation on larval and adult zebrafish fin development. Following the chemo/genetic ablation of these cells, zebrafish display actinotrichia, fin fold, and fin ray defects supporting the hypothesis the defects in distal fin mesenchyme may have contributed to the loss of dermal fin rays during tetrapod evolution. Previous research has shown that changes in the regulation of the 5’HoxA/D genes may have had consequences for both actinodin regulation and the migration of distal fin fold mesenchyme. Chapter IV of this thesis examines the contributions of Hoxa11 regulatory changes to the evolution of the pentadactyl, or five-digit state, in tetrapods. Through a novel tetrapod-specific enhancer, Hoxa11 is repressed from the presumptive limb autopod region in mice. In fish, hoxa11b is expressed distally and ectopic expression of Hoxa11 in the distal limb bud produces mice with polydactyly (extra digits), an ancestral tetrapod character state. In conclusion, we have provided evidence that actinotrichia defects (potentially though changes in actinodin regulation) and fin fold mesenchyme defects may have contributed to the loss of fin dermal bone during the fin-to-limb transition. Our data also shows these two events may have been linked as fin fold mesenchyme require actinotrichia to migrate correctly, while actinotrichia maintenance relies on Actinodin secretion from fin fold mesenchyme. Furthermore, we have also contributed to the growing body of evidence that proposes changes in 5’HoxA/D regulation during the fin-to-limb transition underlie changes in appendicular dermal and endochondral bone. Therefore, it is possible that modifications in shared gene regulatory networks underlie both dermal and endochondral bone evolution during the fin-to-limb transition.
Keywords: Actinodin; 5'HoxA/D; Fin-to-limb transition; Regulatory conservation; Regulatory divergence